ショウライ ノ ニチゴウ ナンキョク ケンキュウ キョウリョク タイセイ ニ カンスル ワークショップ - 川口, 創; カワグチ, ソウ; 白石, 和行; シライシ, カズユキ; Kawaguchi, So; Shiraishi, Kazuyuki (2008)
P(論文) 日豪両国間における南極研究の情報交換ならびに将来への協力関係の更なる発展と強化に資する目的で日豪南極研究協力体制に関するワークショップが2008年6月12日、オーストラリア南極局から4名、国立極地研究所から10数名の研究者の参加のもと開催された。研究協力、プロジェクトの検討及びその合意に向けて、さらにそれを両国の研究計画に反映させるためには、さらなる実務レベルでの話し合いが必要であるとの認識で一致した。本ワークショップは2009年前半までに日豪南極研究合同セミナーを開催する必要がある旨合意した。 A workshop on future Australian-Japanese Antarctic cooperation was held on 12 June 2008 to exchange scientific information and to initiate a dialog to explore the way forward to further enhance and strengthen collaboration in Antarctic science between the two nations. The workshop was attended by four Australian Antarctic Division (AAD) scientists and more than ten National Institute of Polar Research (NIPR) scientists. Through a series of presentations detailing both countries' projects, and the following discussion, the workshop agreed that there are compelling reasons for holding a joint seminar between Australia and Japan by early next year to prioritize and agree to areas of collaboration, and outline the sorts of projects to be reflected in research plans of both countries. departmental bulletin paper